The effectiveness of school administration in improving the teaching performance of Elementary school’s teachers in Irbid Governorate from the teachers’ point of view - Abdulraheem, Suheir JadAllah (Journal of Educational and Psychological Sciences, 2022)
The study aimed to identify the effectiveness of school administration in improving the teaching performance of Elementary stage teachers in Irbid Governorate, and the impact of variables (educational qualification, experience); In the sample estimates of the degree of effectiveness of the school administration in improving teaching performance. The researcher used the descriptive survey method, and the tool consisted of a questionnaire consisting of (32) items distributed over four areas that were applied to a stratified random sample of (218) female teachers in schools in Irbid First Directorate of Education. The sample’s point of view- got an overall average (3.35 out of 5), i.e. with a (medium) degree of effectiveness and at the level of the domains; The field of female teachers’ performance got the highest average (3.49), followed by the field of planning with an average of (3.46), the field of students with an average of (3.49), all of them with a degree of effectiveness (great), and finally the field of managing student and school activities with an average of (2.96) with an average rating of (medium). The results of the study showed that there were statistically significant differences at the level (a≤ 0.05) between the estimates of the study sample members of the effectiveness of the school administration in improving school performance in the four fields of study and on the tool as a whole in favor of an academic qualification less than a bachelor’s degree. And according to the variable of experience in favor of those with experience of 10 years or more Based on the results, the researcher presented a number of recommendations and proposals to improve the effectiveness of school administration in improving the teaching performance of Elementary school teachers in Irbid governorate, and all governorates in the Kingdom.